Magnetic Structures and Turbulence in SN 1006 Revealed with Imaging X-Ray Polarimetry - Zhou Ping; Prokhorov Dmitry; Ferrazzoli Riccardo; Yang Yi-Jung; Slane Patrick; Vink Jacco; Silvestri Stefano; Bucciantini Niccolò; Reynoso Estela; Moffett David; Soffitta Paolo; Swartz Doug; et al. (Institute of Physics, 2025)
Young supernova remnants strongly modify the surrounding magnetic fields, which in turn play an essential role in accelerating cosmic rays (CRs). The X-ray polarization measurements probe magnetic field morphology and turbulence at the immediate acceleration site. We report the X-ray polarization distribution in the northeastern shell of SN 1006 from a 1 Ms observation with the Imaging X-ray Polarimetry Explorer. We found an average polarization degree of 22.4% ± 3.5% and an average polarization angle of −45°.4 ± 4°.5 (measured on the plane of the sky from north to east). The X-ray polarization angle distribution reveals that the magnetic fields immediately behind the shock in the northeastern shell of SN 1006 are nearly parallel to the shock normal or radially distributed, similar to that in the radio observations, and consistent with the quasi-parallel CR acceleration scenario. The X-ray emission is marginally more polarized than that in the radio band. The X-ray polarization degree of SN 1006 is much larger than that in Cas A and Tycho, together with the relatively tenuous and smooth ambient medium of the remnant, favoring that CR-induced instabilities set the magnetic turbulence in SN 1006, and CR acceleration is environment-dependent.